Field-induced magnetic phase transitions and memory effect in bilayer ruthenate Ca3Ru2O7 with Fe substitution. (23rd January 2018) - Zhu, M; Hong, T; Peng, J; Zou, T; Mao, Z Q; Ke, X
Abstract: Bilayer ruthenate Ca3 (Ru1− x Fe x )2 O7 ( x   =  0.05) exhibits an incommensurate magnetic soliton lattice driven by the Dzyaloshinskii–Moriya interaction. Here we report complex field-induced magnetic phase transitions and memory effect in this system via single-crystal neutron diffraction and magnetotransport measurements. We observe first-order incommensurate-to-commensurate magnetic transitions upon applying the magnetic field both along and perpendicular to the propagation axis of the incommensurate spin structure. Furthermore, we find that the metastable states formed upon decreasing the magnetic field depend on the temperature and the applied field orientation. We suggest that the observed field-induced metastability may be ascribable to the quenched kinetics at low temperature.